Relevansi Kebijakan Kurikulum Merdeka Dengan Pendidikan Abad 21 Pada Pembelajaran IPS di SD - Ai Nurul Nurohmah; Dewi Kartini; Tin Rustini (Peneliti.net, 2023)
The purpose of this study is to find out whether there is relevance to the independent curriculum policy with 21st century education in social studies learning. During the Covid 19 pandemic, learning became less effective due to distance learning (PJJ). That's why there was a learning crisis or commonly known as learning loss and also a learning gap which is commonly referred to as the learning gap. Efforts to overcome this, the Ministry of Education and Culture officially launched a new curriculum, namely the independent curriculum. This independent curriculum has begun to be implemented in schools. In social studies learning in elementary schools in the independent curriculum there is a change, namely the enactment of natural sciences, namely the combination of science and social studies subjects. Education currently requires students to have 21st century competencies, namely communication, creativity and innovation, critical thinking and problem solving, and collaboration. Researchers use qualitative methods in answering problems, this research is also supported by literature studies such as books, scientific articles and sources that can be accounted for. The results of this study state that the independent curriculum in social studies learning in elementary schools is relevant to 21st century education, because it fulfills the principles of 21st century learning and can develop 21st century skills in accordance with the objectives of the independent curriculum, namely forming a profile of Pancasila students